2019
DOI: 10.1536/ihj.17-293
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Necrosis Factor-α Gene Polymorphism (G-308A) and Dilated Cardiomyopathy

Abstract: The issue that genetic polymorphism of tumor necrosis factor-α (TNF-α) is associated with dilated cardiomyopathy (DCM) is debatable. We sought to investigate the potential role of TNF-α gene polymorphism (G-308A) in the susceptibility to dilated cardiomyopathy. We retrieved PubMed, EMBASE, and CNKI to collect all articles which reported on the association between TNF-α G-308A polymorphism and dilated cardiomyopathy. Two authors used the Newcastle-Ottawa Scale (NOS) checklist to assess the quality of the includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 45 publications
(46 reference statements)
0
3
0
Order By: Relevance
“…Tumor necrosis factor-α is a pro-inflammatory cytokine produced by activated macrophages and monocytes. Different studies have demonstrated the role of TNF-α in the pathophysiology of atherosclerosis, myocardial infarction and chronic heart failure [ 35 , 36 , 37 ]. Elevated TNF-α levels have also been found in patients with DCM, which indicates that TNF-α may be related to the pathogenesis of dilated cardiomyopathy [ 36 ].…”
Section: Inflammatory Biomarkersmentioning
confidence: 99%
See 1 more Smart Citation
“…Tumor necrosis factor-α is a pro-inflammatory cytokine produced by activated macrophages and monocytes. Different studies have demonstrated the role of TNF-α in the pathophysiology of atherosclerosis, myocardial infarction and chronic heart failure [ 35 , 36 , 37 ]. Elevated TNF-α levels have also been found in patients with DCM, which indicates that TNF-α may be related to the pathogenesis of dilated cardiomyopathy [ 36 ].…”
Section: Inflammatory Biomarkersmentioning
confidence: 99%
“…Based on all these data, a recent metanalysis, which included nine eligible studies (1338 patients and 1677 controls), evaluated the possible association between TNF-α gene polymorphism (G-308A) and susceptibility to DCM. The main result of this metanalysis is that TNF-α gene polymorphism (G-308A) may have an important role in the pathogenesis and progression of dilated cardiomyopathy, especially in Asian populations [ 35 ]. However, to date, there are no studies on the implications of TNF-α in risk stratification of patients with DCM.…”
Section: Inflammatory Biomarkersmentioning
confidence: 99%
“…To confirm that, TNF-α was used as a treatment and resulted in a dose-and time-dependent decrease in mRNA levels of dystrophin and titin (40). Other studies supported this hypothesis, where they revealed that TNFα gene polymorphism (G-308A) might play a key role in the susceptibility to dilated cardiomyopathy (41).…”
Section: Genes Encoding Sarcomeric Proteins-ttn (Titin) Mutationsmentioning
confidence: 94%